Collaborating Digital World - Anastasia Suen (United States Crabtree Publishing Co,US, 2018)
This informative title emphasizes the benefits of collaboration to learning, using digital technologies. Connecting with others of different backgrounds, culture, or expertise allows readers to share their knowledge and perspective, broaden their understanding, and find the best solutions possible. Readers will learn how to be positive contributors working as part of a team toward a common goal. Inspiring, mini-bios highlight young people collaborating to create positive social change.
Keywords: Digital Media; PY-UOI - How we Organize Ourselves